(untitled) (Educational Knowledge, 2022)
The Coronavirus (COVID-19) pandemic disrupted most human activities. Business failures led to job losses, and this, coupled with the fear of illness and the lack of a coherent and coordinated response to this devastating situation, has impacted people’s well-being and mental health. The actions taken to stop the spread of the virus changed our way of life. Mandatory isolation, the closure of schools and other educational centers, and the closure of workplaces and other activities have led to the strengthening and development of digital environments: online education, teleworking, streaming cultural consumption, online shopping, etc. Pre-pandemic education and learning models collapsed, making more flexible and inclusive parameters necessary. Skills that help us adapt to these new realities and flexibly handle challenging situations are crucial, enabling individuals to overcome adversity and emerge stronger. All of this stems from a personal effort of continuous learning, as well as from the sphere of citizenship, through associations that join forces to move forward in the midst of this crossroads.